Taupō: an overview of New Zealand's youngest supervolcano. Issue 2 (3rd July 2021) - Barker, Simon J.; Wilson, Colin J.N.; Illsley-Kemp, Finnigan; Leonard, Graham S.; Mestel, Eleanor R.H.; Mauriohooho, Kate; Charlier, Bruce L.A.
ABSTRACT: Taupō volcano (New Zealand) is distinguished as the source of Earth's youngest supereruption (∼25.5 ka), with Lake Taupō occupying the resulting caldera. Taupō has also produced eruptions of a wide variety of sizes, styles and associated landscape responses over a ∼350 kyr period. Early Taupō (>54 ka) is poorly demarcated, merging with Maroa to the north, and is represented by widely scattered, geochemically distinct, effusive domes and explosive eruption products from vents all around the modern lake. Taupō had two independent magmatic systems from 54–25.5 ka, one that led to the Oruanui event focussed beneath the area of the modern lake and a second, northeast of the lake that has remained active to the present. Following the Oruanui supereruption, the rebuilt modern hyperactive Taupō magmatic system is primarily focussed beneath the lake and has generated 25 rhyolitic eruptions since ∼12 ka. The young rhyolite magmas come from an evolving silicic magma reservoir, but vary widely in their eruptive sizes and destructive potential. In the modern era Taupō experiences unrest every decade or so, but uncertainties remain over the nature of the magma reservoir and the processes that drive unrest or eruptive activity that require new geophysical data and interpretations.